PROGRAM PENDAMPINGAN UKM LAUDIA KACANG KOTA CIMAHI - Yayan Firmansyah; Teguh Iman Basuki; Faiz Said Bachmid (Institut Informatika dan Bisnis Darmajaya, 2019)
UMKM are one of the sectors that can sustain the Indonesian economy due to absorbing very large employment opportunities. Besides that, UMKM are also a sector that is immune to economic crises, if we flash back almost 20 years ago when our nation experienced a multidimensional crisis. Where at that time many companies both international and national scale were out of business, it was proven that UMKM could survive at that time. Laudia was one of the UMKMs fostered by Studentpreneur STIE Ekuitas having its address at Cimahi City. Kacang Laudia UMKM Cimahi City has two product variations, namely egg glass and onion beans. From the results of the initial survey of the field writer and interview with Ms. Siti Mudrikah, the owner of Kacang Laudia UMKM. We get an overview of business processes, starting from the challenges, obstacles, opportunities and threats of these UMKM, so that we get a complete picture of how to implement business processes, here we prioritize some who need immediate improvement: 1. Need training and mentoring with increase in sales volume 2. The production process needs to be improved and 3. Recording of financial statements. We hope that this will be carried out by community service staff to increase sales volume, productivity efficiency and good simple financial reporting.Keywords: UMKM